Outcome of Burn Management in Bangkok Hospital - Nitiphon, Att; Muangman, Pornprom; Omnoi, Jiranan; Maneechay, Suchada (The Bangkok Medical Journal, 2012)
OBJECTIVES. To report the result of major burn treatment in Bangkok Hospital. MATERIALS AND METHODS. All major burn cases were debrided and dressed with antiseptic procedures and antiseptic cream under supervised teamwork. We retrospectively reviewed all cases from July 2007 to December 2010. RESULTS. Sixty burn patients, the average age 33.17 year percent of total body surface area (% TBSA) was 34.9, Baux score was 74.93. CONCLUSION. Mortality was compatible with Baux score.